Performance Analysis of DN1750 and DN1800 Electric Submersible Pump for Production Optimization on the Oil Well - Agung Wahyudi Biantoro; Bambang Darmono; Hadi Pranoto (Institute for Research on Innovation and Industrial System (IRIS), 2022)
Abstract. Electric Submersible Pump (ESP) is an artificial lift method to lift fluid from the reservoir to the surface with a certain production rate, the ability of the pump to lift a certain fluid to the surface is adjusted to the capacity of the well itself. Over time, the production of oil wells will experience a decrease in the rate of production which will cause a decrease in pump performance. In several oil wells, well maintenance activities have been carried out. Therefore, in this study, an analysis of pump performance and optimization of the ESP pump was carried out using the Nodal Variable Speed Drive analysis method. The goal is to determine the production capacity of the oil well and determine the pump speed as desired. Oil well performance analysis and optimization of the ESP pump were carried out by mathematical calculations with the optimization results obtained that the DN1750 pump was installed at a frequency of 50 Hz, 55 Hz, 60 Hz, 65 Hz, and 70 Hz. The Hz number does not cross the desired flow rate line (q optimum) or is outside the desired fluid flow rate range by the oil well so it can be interpreted that based on the observation of the optimization process, the condition of the DN1750 pump is not working optimally so that the oil production capacity is not optimal. The DN 1800 pump at a frequency of 55 Hz with a speed of 3300 rpm is in accordance with the production capabilities of oil wells so that the appropriate pump is obtained and is expected to work at optimum conditions. At a frequency of 55 Hz with a speed of 3300 rpm successfully cut the desired flow rate line (q optimum) from the observed oil well characteristics or is in the range of fluid flow rates desired by the oil well, which is 1936,698 Barrels Per Day (BPD) with wellbore pressure (PWF) 629 psi.